MACHINING DIFFICULTIES AND DETERMINANT MACHINING PARAMETERS FOR TITANIUM ALLOY - M.S.M Yusop , A.Y.M. Said , Z. Karim, A.S. Ramli, I.H.A. Razak, M.Z.A Yazid (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Titanium is a major material for aircraft parts and components, particularly the body and engines. This material offers rigidity, strength and light in weight, that are significant in improving the payload capacity as well as fuel consumption of the jet engines. However, few restraints were identified in machining of titanium. The hard properties of this material which require high machining force, in addition the elasticity and poor thermal conductivity causing the machining of titanium parts becomes expensive and difficult. Due to these issues, proper important machining parameters were discuss to ensure the output of the machining is at optimum with the most cost effectiveness. These parameters were further discussed in this paper, reviewed from the various research paper and works, past research experiences and series of discussion with the titanium machining experts were explained and summarized.